Edukasi Indonesia Bersinar (Bersih dari Sindikat Narkoba) Menuju ASEAN Free Drugs 2025 Bagi Mahasiswa Universitas Nahdatul Ulama Kalimantan Barat - Alunaza, Hardi; Nuzulian, Ully; Rohilie, Haunan Fachry; Almutahar, Hasan; Mentari, Mentari (Abdimas Mandalika, 2025)
Abstract:  This community service activity is based on the need for students to gain education about Indonesia's strategic role in combating drug abuse, regional regulations to achieve ASEAN Free Drugs 2025, and the importance of youth as agents of change and social control in tackling drug trafficking and abuse. The community service activity is conducted in the Sungai Raya District of Kubu Raya Regency with the aim of providing education about Indonesia being free from drug syndicates towards ASEAN Free Drugs 2025. It will take time from May to August 2024, with activities including socialization, discussions game session, as well as documentation and reporting. The first sub-topic of the education covers three strategic steps in combating drugs: a soft approach involving preventive activities, a hard approach with firm actions, and a smart power approach. The second topic addresses the ASEAN Work Plan in achieving ASEAN Free Drugs 2025. Additionally, there will be socialization regarding youth as agents of change and social control by fostering good habits in the community to combat drug abuse.Abstrak: Kegiatan pengabdian ini didasari bahwa mahasiswa perlu mendapatkan edukasi mengenai peran strategis Indonesia dalam memberantas penyalahgunaan narkoba, regulasi regional dalam mewujudkan ASEAN Free Drugs 2025 dan pemahaman mengenai pentingnya peran pemuda sebagai agent of change dan agent of social control dalam memberantas peredaran dan penyalahgunaan narkoba. Kegiatan pengabdian ini dilaksanakan di Kecamatan Sungai Raya Kabupaten Kubu Raya dengan tujuan memberikan edukasi mengenai Indonesia bersih dari sindikat narkoba menuju ASEAN Free Drugs 2025. Kegiatan pengabdian ini dilaksanakan mulai dari Mei hingga Agustus 2024 dengan bentuk pelaksanaan kegiatan terdiri dari penyampaian materi, diskusi dan game edukasi, serta dokumentasi dan pelaporan. Edukasi mengenai sub-materi pertama yakni tiga langkah strategis dalam memberantas narkoba yakni soft appoarch dengan pendekatan berupa aktivitas pencegahan, hard approach dengan tindakan tegas, dan smart power approach. Kedua, ASEAN Work Plan guna mewujudkan ASEAN Free Drugs 2025. Serta, sosialisasi terkait pemuda sebagai agent of change dan agent of social control dengan membangun kebiasaan baik di lingkungan dalam memberantas penyalahgunaan narkoba.